PEMBERDAYAAN EKONOMI KREATIF MASYARAKAT MELALUI PENGOLAHAN MAKANAN PADA POKDARWIS DESA WISATA SIDOMULYO KECAMATAN SILO KABUPATEN JEMBER - Anggraini, Cristian Rizqi; Nusanto, Baktiawan (Jurnal Abdi Insani, 2024)
Sidomulyo Village, Silo District, is one of the villages whose residents mostly work as farmers in Jember Regency. The obstacle faced by the community is that the garden products obtained by farmers have relatively low and moderate selling prices. An alternative solution that can be taken to overcome these obstacles is to provide education and assistance in processing farmers' garden products. The aim of this program is to provide education to the people of Sidomulyo Village through POKDARWIS and provide assistance in processing food and drinks from the gardens of Sidomulyo Village residents. The methods used are program preparation, outreach and training, product creation, utilization, monitoring and evaluation. The result of this program is a processing and marketing group that has the potential to produce food and beverages or increase the selling value of products so that people can produce processed food and beverage products that have high economic value to improve the community's economy. And it can be used as a typical food from Sidomulyo Village.